Pentraxin-3 – a potential biomarker in ANCA-associated vasculitis. (4th May 2023) - Jonasdottir, AD; Antovic, A; Qureshi, AR; Nordin, A; Malmström, V; Gunnarsson, I; Bruchfeld, A
Abstract : Objective: The aim of this study was to investigate pentraxin-3 (PTX3) as a potential biomarker of inflammatory activity in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) at baseline and 6 month follow-up in a longitudinal cohort. Method: Plasma PTX3 levels were measured in 79 newly diagnosed or relapsing AAV patients at baseline and 6 month follow-up, and in 23 healthy controls. Urinary PTX3 levels were measured in 34 of the patients. C-reactive protein (CRP), creatinine, and albuminuria were measured and the cumulative glucocorticoid dose at inclusion was calculated. The Birmingham Vasculitis Activity Score (BVAS) was assessed at baseline and follow-up. Results: Plasma PTX3 levels were significantly higher at baseline than at 6 months (2.85 vs 1.23 ng/mL, p < 0.001). Plasma and urinary PTX3 levels correlated with BVAS at baseline (ρ = 0.45, p < 0.001, and ρ = 0.49, p = 0.008, respectively). A significant correlation between both plasma and urinary PTX3 levels and estimated glomerular filtration rate and albuminuria was found. However, there was no correlation between plasma and urinary PTX3 levels. At baseline, plasma and urinary PTX3 levels were significantly higher in patients with kidney involvement. PTX3 levels did not correlate with CRP, nor was there a correlation between CRP levels and BVAS at baseline. Conclusion: Plasma and urinary PTX3 seem to reflect disease activity in AAV better than the commonly used CRP. PTX3 may have a potential role as a biomarker in monitoring disease activity in AAV patients, particularly in patients with kidney involvement.